Answer:
following are the solution to this question:
Explanation:
Please find the complete question in the attached file.
![\lim_(x\to 2)+f(x) = \lim_(x\to 2)+ (ax^2-bx+3) = 4a-2b+3\\\\ \to 4a-2b+3 = 4\\\\ \therefore \ \ 4a-2b = 1\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/jko6fli6z038ycaxrqp8oechjpgiaoa7aa.png)
The one-sided limits of F(x) at x = 3 must be equivalent for f(x) to be continuous at x = 3.
So,
![\to 9a-3b+3 = 6-a+b\\\\\therefore\\ \to 10a -4b = 3](https://img.qammunity.org/2021/formulas/mathematics/college/2gv3q1wbwtxqd5u9d8uf2uyfquinrowliq.png)
![\to 4a - 2b = 1......(a)\\\to 10a - 4b = 3.......(b)\\](https://img.qammunity.org/2021/formulas/mathematics/college/f5jfuot18f6zzfxfmz5nu5g2lr0wdzdl1c.png)
In equation a multiply the by -2 and then add in the equation b:
So, the value of